Análise dos parâmetros antropométricos da cabeça dos militares da força aérea brasileira no projeto de capacetes balísticos - Alves, Henrique Averaldo; Santos, Maria Isabel Manfredini de Paula; Monteiro, Marco Aurélio Alvarenga [UNESP]; Moraes, Paulo Renato; Melo, Francisco Cristóvão Lourenço de; Ribeiro, Wellington (My University, 2011)
The study of the physical man characteristics and their variations have caught the man's interests since the ancient age. In Brazil, there are no studies which define the anthropometric profile of the Brazilian's head, hindering the development of ergonomic designs. One problem that occurs in the Brazilian armed forces is the use of protective helmets made with measurements of other countries, which causes great discomfort. Thus, this study aims to conduct a study to determine the anthropometric measurements of the head of the Brazilian Air Force military, assisting in the production of helmets more suitable. Therefore, it is presented ananthropometric survey in 576 students of the School of Aeronautics Expert, 286 females and 290 males, aged between 17 and 36 years. The study showed that the differences found between genders are less than 5%. In addition to the fact that the helmet Tues adjustments, there is no need for production of different helmets in relation to gender, but some changes are necessary measures in circumference and shape of the helmet.

O estudo das características físicas do homem e suas variações tem interessado ao homem desde a antiguidade. No Brasil ainda não existem estudos que definam o perfil antropométrico da cabeça dos brasileiros, dificultando o desenvolvimento de projetos ergonômicos. Um dos problemas que ocorre nas Forças Armadas brasileiras é o uso de capacetes de proteção confeccionados com medidas de outros países, os quais acarretam grande desconforto. Desta forma, este trabalho tem como objetivo realizar um estudo para apurar as medidas antropométricas da cabeça de militares da Força Aérea Brasileira, auxiliando na produção de capacetes mais adequados. Para tanto, é apresentado um levantamento antropométrico em 576 alunos da Escola de Especialistas de Aeronáutica, 286 do gênero feminino e 290 do gênero masculino, com idade entre 17 e 36 anos. O estudo demonstrou que as diferenças encontradas entre os gêneros são inferiores a 5%. Somando-se ao fato de o capacete ter regulagens, não há a necessidade da produção de capacetes diferentes em relação ao gênero, porém são sugeridas algumas alterações nas medidas de circunferência e formato do capacete.
Analysis of anthropometric parameters head of the brazilian air force military project ballistic helmets
Keywords: Anthropometry of the head; Ballistic helmets; Ergonomics; Antropometria da cabeça; Capacetes balísticos; Ergonomia